(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2025)
Background: Patient Prosthesis Mismatch (PPM) after surgical aortic valve replacement may exacerbate patient’s symptoms which is worsened If coupled with coronary artery occlusion. Very few re-operations were reported in our population to correct such pathologies and to our best knowledge a repeat re-do (Tri-do) was never reported in our country. Case Presentation: We hereby present a patient’s report who was previously treated twice by Aortic Valve Replacement (AVR) and yet he was not relieved of PPM. To make things worse he also developed left main coronary artery occlusion and we had to perform a tri-do AVR with coronary artery bypass grafting and aortic root enlargement. Conclusion: Our well-planned surgery with valiant efforts from the team members made the surgery very worthy for the patient as he was relieved of symptoms. Surgeons with skills and experience should perform this type of life saving surgery without much hesitations if everything permits. JCMCTA 2024 ; 35 (1) : 172-175